1994
DOI: 10.1007/bf03164987
|View full text |Cite
|
Sign up to set email alerts
|

On clinical usefulness of Tl-201 scintigraphy for the management of malignant soft tissue tumors

Abstract: The purpose of this study was to investigate Tl-201 as a tumor scanning agent in patients with malignant soft tissue sarcomas and to establish the sensitivity of this type of scintigraphy concerning local recurrences or metastases that may remain clinically suspected. Seventy-eight patients with malignant soft tissue sarcomas and 22 with benign soft tissue tumors were studied. Of these 78 malignant soft tissue sarcomas patients, the sensitivity of Tl-201 (81.2%) was higher than that of Ga-67 (68.8%). Thirty-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…In musculoskeletal tumors, 201 Tl scintigraphy has been reported to be useful for differentiating benign from 13 In the current case, the tumor showed faint 201 Tl uptake, which also made the differential diagnosis from liposarcoma difficult. In the current case report, CT images demonstrated nonadipose areas within the tumor that were moderately enhanced on the delayed phase compared with the early phase after administration of contrast medium.…”
Section: Discussionmentioning
confidence: 70%
“…In musculoskeletal tumors, 201 Tl scintigraphy has been reported to be useful for differentiating benign from 13 In the current case, the tumor showed faint 201 Tl uptake, which also made the differential diagnosis from liposarcoma difficult. In the current case report, CT images demonstrated nonadipose areas within the tumor that were moderately enhanced on the delayed phase compared with the early phase after administration of contrast medium.…”
Section: Discussionmentioning
confidence: 70%
“…A review of studies published in the last 10 years revealed a total of 19 synovial sarcomas from six separate studies that have been evaluated with scintigraphy 1−6 . Delayed Tl images showed significant tumour uptake in 7/10 cases 1,4,5 . This compares with 9/10 in our experience (Table 1).…”
Section: Discussionmentioning
confidence: 50%
“…This compares with 9/10 in our experience (Table 1). Gallium (1/6 cases) 1,5,6 appears less useful in detecting synovial sarcoma and 99m Tc‐sestamibi 3 , 99m Tc‐pertechnetate 4 , and 99m Tc‐DMSA‐V 6 have shown uptake in occasional cases. 99m Tc‐methylene diphosphonate bone scan may show uptake in synovial sarcoma, particularly if there is calcification within the lesion 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…We considered that no statistical significance of WR might be due to relatively small volume of bone lesion compared with surrounding soft tissue and the change of 201Tl uptake to the surrounding muscle had the bigger impact on WR in both benign and malignant bone lesions. According to the previous reports [2,4,7,11,[14][15][16][17][18][19][20][21], 201Tl uptake depends on cell viability and metabolic condition and a high metabolic rate with malignancy was the most important factor determining differences in 201Tl uptake between malignant tumors and benign lesions. Moreover, 201Tl uptake on early imaging is affected by tumor vascularity and cellularity.…”
Section: Discussionmentioning
confidence: 97%